Electrocorticographic Temporal Alteration Mapping: A Clinical Technique for Mapping the Motor Cortex with Movement-Related Cortical Potentials - Wu, Zehan; Xie, Tao; Yao, Lin; Zhang, Dingguo; Sheng, Xinjun; Farina, Dario; Chen, Liang; Mao, Ying; Zhu, Xiangyang (Frontiers in Neuroscience, 2017)
In this work, electrocorticographic temporal alteration mapping (ETAM) was proposed for motor cortex mapping by utilizing movement-related cortical potentials (MRCPs) within [0.05 3] Hz low frequency band. This MRCP waveform-based temporal domain approach was compared with the state-of-the-art electrocorticographic frequency alteration mapping (EFAM), which was based on high frequency spectrum dynamics. Five patients (2 epilepsy cases and 3 tumor cases) were enrolled in this study. Each patient had intraoperative direct electrocortical stimulation (DECS) procedure for motor cortex localization, and the patient was required to perform simple brisk wrist extension task during awake craniotomy surgery. Cross-validation results shown that the proposed ETAM method had a high performance in sensitivity (81.82%) and specificity (94.33%) for identifying sites which exhibited positive DECS motor responses. No significant difference in sensitivity was observed between ETAM and EFAM methods. However, the proposed ETAM was much higher in specificity as compared with EFAM (94.33% vs. 86.08%). Our results indicated that for the intraoperative functional brain mapping, ETAM was a promising novel approach for motor cortex localization and had a great potential to reduce the needs for cortical electrical stimulation.